AIAA Atmospheric Flight Mechanics Conference 2011
DOI: 10.2514/6.2011-6542
|View full text |Cite
|
Sign up to set email alerts
|

Handling Qualities of a Blended Wing Body Aircraft

Abstract: The blended wing body (BWB) is a tailless aircraft with the potential to use 27% less fuel than a conventional aircraft with the same passenger capacity and range. The primary purpose of the current study was to determine the handling qualities of the BWB, using piloted-handling trials in a moving-base simulator. The secondary purpose was to determine the effect of simulator motion on handling-quality ratings. De Castro conducted piloted-handling trials in a fixed-base simulator. De Castro's tasks and flight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For example, the trailing-edge surfaces may consist of a body flap inner and outer flaps and ailerons that may be used for lift, pitch or roll control. The present work extends existing knowledge on the subject in two directions: (i) on theoretical side (10)(11)(12)(13) by allowing for the deflections of multiple control surfaces, that gives more options to obtain the desired forces or moments with less risk of flow separation or aeroelastic effects; (ii) on the application side (14)(15)(16)(17) by considering not only minimum drag but also maximum drag (e.g. for fast descent) and maximum control moments for emergencies, such an engine-out condition.…”
Section: Introductionmentioning
confidence: 88%
“…For example, the trailing-edge surfaces may consist of a body flap inner and outer flaps and ailerons that may be used for lift, pitch or roll control. The present work extends existing knowledge on the subject in two directions: (i) on theoretical side (10)(11)(12)(13) by allowing for the deflections of multiple control surfaces, that gives more options to obtain the desired forces or moments with less risk of flow separation or aeroelastic effects; (ii) on the application side (14)(15)(16)(17) by considering not only minimum drag but also maximum drag (e.g. for fast descent) and maximum control moments for emergencies, such an engine-out condition.…”
Section: Introductionmentioning
confidence: 88%
“…There is a direct pre-assigned relation between the flight control surfaces and the pilot input. The same BWB configurations were further studied by means of piloted simulation using a motion base simulator by Peterson and Grant [30]. Roysdon and Khalid [31] studied the lateral-directional stability of a small business jet BWB using computational fluid dynamics and flight simulation and found that good controllability can be achieved.…”
Section: Introductionmentioning
confidence: 99%